2006
DOI: 10.1021/jf062517l
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Heat Treatment on the Phenolic Compounds and Antioxidant Capacity of Citrus Peel Extract

Abstract: This paper reports the effects of heat treatment on huyou (Citrus paradisi Changshanhuyou) peel in terms of phenolic compounds and antioxidant capacity. High-performance liquid chromatography (HPLC) coupled with a photodiode array (PDA) detector was used in this study for the analysis of phenolic acids (divided into four fractions:  free, ester, glycoside, and ester-bound) and flavanone glycosides (FGs) in huyou peel (HP) before and after heat treatment. The results showed that after heat treatment, the free f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
235
1
11

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 376 publications
(275 citation statements)
references
References 27 publications
28
235
1
11
Order By: Relevance
“…Moreover, the temperature for polyphenol extraction, as well as the incubation time, also contributes to the efficacy of the antioxidant activity [42][43][44]. However, contradicting the above results, few studies also suggested that the total amount of phenolic acids and flavonoids decreased after heat treatment [45,46]. This indicated that some phenolic acids probably are heat labile, whereas others are converted from insoluble phenolic compounds to soluble phenolics after heat treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the temperature for polyphenol extraction, as well as the incubation time, also contributes to the efficacy of the antioxidant activity [42][43][44]. However, contradicting the above results, few studies also suggested that the total amount of phenolic acids and flavonoids decreased after heat treatment [45,46]. This indicated that some phenolic acids probably are heat labile, whereas others are converted from insoluble phenolic compounds to soluble phenolics after heat treatment.…”
Section: Discussionmentioning
confidence: 99%
“…But, the differences among the production stages were not significant, statistically. Xu et al (2007) reported that free fraction of phenolics increased, whereas ester, glycoside, and ester-bound fractions decreased after heating. Moreover, there was a decrease of total phenolic acid content after heat treatment and the content of four flavanone glycosides (narirutin, naringin, hesperidin, and neohesperidin) declined with heating time and temperature.…”
Section: Resultsmentioning
confidence: 99%
“…For example, polyphenols at an intermediate oxidation state can exhibit higher radical scavenging activity than the completely nonoxidized ones (Nicoli et al 1999;Polydera et al 2004). Xu et al (2007) assumed that many antioxidant phenolic compounds in plants are usually presented as the covalently-bound form; therefore, some processing methods were employed to liberate them in order to enhance their antioxidant capacity. Seok-Moon et al (2004) reported that heat treatment may liberate some low molecular weight in phenolic compounds and increase the antioxidant capacity of citrus peel as a result.…”
Section: Resultsmentioning
confidence: 99%
“…These conditions resulted in the highest values for DS and phenolic content (4.65 and 119.1 mg GAE/g, respectively) at 2.5 h. This indicated that the esterification time extension contributed to an improvement in the esterification effect as well as the DS and phenolic content of the polysaccharides. However, flavonoids might be damaged due to partial degradation-induced ester bond and glycosidic bond rupture, as a result of a decrease in solvent amount caused by a peracid condition and an excessive esterification time (Xu, Ye, Chen, & Liu, 2007). Thus, phenolic acid distribution was altered, leading to decreases in the esterification degree and phenolic concentration.…”
Section: The Effect Of Dmf Amount On Ds and Phenolic Contentmentioning
confidence: 99%